Coronary total occlusion and minimalist approach: When less is more. Issue 5 (20th January 2020) - Musumeci, Giuseppe; Baralis, Giorgio
Key Points: The minimalistic hybrid algorithm is a possible alternative sequence of steps in the setting of coronary total occlusion (CTO) recanalization. A fully transradial approach in CTO is a valid alternative to transfemoral approach with a high rate of success. A minimalistic hybrid algorithm maintains all the available possible options for crossing the CTO lesions.